2006
DOI: 10.1124/dmd.106.012922
|View full text |Cite
|
Sign up to set email alerts
|

Triethylenetetramine and Metabolites: Levels in Relation to Copper and Zinc Excretion in Urine of Healthy Volunteers and Type 2 Diabetic Patients

Abstract: ABSTRACT:Triethylenetetramine (TETA), a selective Cu II -chelator used in the treatment of Wilson's disease, is now undergoing clinical trials for the treatment of heart failure in diabetes. Despite decades of clinical use, knowledge of its pharmacology in human subjects remains incomplete. Here, we first used liquid chromatographymass spectrometry (LC-MS) to detect and identify major metabolites of TETA in human plasma and urine, and then used this method to measure concentrations of TETA and its metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Metabolite(s) recovery ranges from 2.50 to 9.00% in healthy volunteers; and, from 8.56 to 27.1% in patients with diabetes or Wilson's disease (Table 2). It is suggested that patients with diabetes have a higher rate of TETA metabolism than healthy volunteers (38). Whether other disease states, such as Wilson's disease or cancer, have the same effect on TETA metabolism as diabetes has not been established, but further investigation is warranted.…”
Section: Metabolism In Humansmentioning
confidence: 99%
See 4 more Smart Citations
“…Metabolite(s) recovery ranges from 2.50 to 9.00% in healthy volunteers; and, from 8.56 to 27.1% in patients with diabetes or Wilson's disease (Table 2). It is suggested that patients with diabetes have a higher rate of TETA metabolism than healthy volunteers (38). Whether other disease states, such as Wilson's disease or cancer, have the same effect on TETA metabolism as diabetes has not been established, but further investigation is warranted.…”
Section: Metabolism In Humansmentioning
confidence: 99%
“…Patients affected with diabetes excrete more metabolites in urine than healthy volunteers (38). It has been reported that urinary excretion of spermine is elevated in patients with certain types of cancer (50,51).…”
Section: Excretion And/or Elimination In Humansmentioning
confidence: 99%
See 3 more Smart Citations